Secrecy, Power, and Solidarity in Prison Code Language: A Phenomenological Analysis of Female Inmates in Tangerang Womens Correctional Facility - Rustini Floranita; Rizaldi Parani; Diana Maharani (INJECT (Interdisciplinary Journal of Communication), 2026)
This article presents the findings of a phenomenological inquiry exploring the life experiences of inmates in the Tangerang Women’s Correctional Facility in using coded language to maintain secrecy, power, and solidarity. Contrary to the traditional view of prisons as static institutions, this study conceptualizes the prison environment as a networked micro-society where language functions as the primary infrastructure for social cohesion. Utilizing Merleau-Ponty’s phenomenology of embodiment and Foucault’s analysis of disciplinary power, data are collected through in-depth interviews with ten inmates and five correctional officers. The study discovered communication patterns where inmates actively used coded language to survive, thrive, and maintain social cohesion within the correctional facility. The study also identified specific warning systems, such as a coded greeting that function as counter-surveillance tactics to maintain women’s autonomy in prison, against internal and external control. Furthermore, power is revealed to be negotiated rather than absolute, mediated through inmate team leaders using numerical codes to disclose the high-level authority. By using this coded language, inmates create a strong sense of community and support, turning the sadness of being locked up into a shared strength. This study proves that prison coded language is more than just a way to hide secrets. It is how inmates hold onto their dignity, maintain solidarity, and keep peace in a place where they have no power. The study concludes that secrecy, power, and solidarity are deeply intertwined in prison life. Further study should expand this phenomenology and explore other’s correctional facilities to compare.